Should external load quantification for female wheelchair basketball be individualised? - Bailey, P.; Retveld, T.; Blagrove, R.; van der Slikke, R.; Goosey-Tolfrey, V. (BASES Conference 2024, 2024)
Quantifying external match load (EML) in wheelchair court sports is vital for effective management of training programs and optimizing competitive performance (Paulson and Goosey Tolfrey, 2017, International Journal of Sports Physiology and Performance, 12, 275 - 286). The aim of this study was to examine the agreement between fixed and individualised (IND) speed zones used to quantify EML and their relationship with internal match load (IML) measures. Following ethical approval, 31 female wheelchair basketball players (age: 28 ± 7 years, experience: 11 ± 5 years, weekly training: 12 ± 4 h) had their EML measured using inertial measurement units (Movesense Active, 52 hz) with one on wheelchair frame, and one on hub of wheel (Rietveld et al, 2019, PLoS ONE, 14). IML was quantified using the summated heart rate (HR) zone method and a session RPE (sRPE) using the Borg CR-10 scale (Borg, 1998). Eleven international players (INT) were observed over 13 friendly international level games (71 observations) and 20 premier league players (WPL) over 1 - 2 games (24 observa tions). The percentage time spent in six speed zones was compared for ARB (<0, 0-1, 1-2, 2-3, 3-4, >4 m.s-1) and IND (<0, 0-20, 20-50, 50-80, 80-95, >95% max velocity) zonal meth ods using an ANOVA. Additionally, absolute time spent in these zones was correlated with IML using Pearson and Spearman Rho correlations in SPSS. The IND method resulted in more time spent in the low-speed zone (Z3), than the fixed method at both international (d = 3.75, 95% CI: -0.03 to 0.02) and WPL (d = 2.63, 95% CI: 0.03 to 0.07) levels (p < 0.001). The fixed method resulted in more time spent in the high (Z5, d = 4.32) and very high (Z6, d = 2.11) zones, compared to the IND method, at both levels (p < 0.001). Greater differences were observed between methods at the INT level (Z5, d = 18.57; Z6, d = 4.89) compared to the WPL level (Z5, d = 4.32, Z6, d = 2.11) (p < 0.025). Both competition levels showed large correlations between zones 2 - 4 and IML using both zonal methods (r = 0.69 - 0.91, 95% CI: > 0.54 to < 0.96). This study highlights discrepancies in EML quantification between the two zonal methods, supporting the need for further research regarding the application of IND speed zones in wheelchair basketball.